2021
DOI: 10.1155/2021/9363569
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Injury Biomarkers and the Risk of Death in Patients with COVID-19: A Systematic Review and Meta-Analysis

Abstract: Background. Cardiac complications may develop in a proportion of patients with the novel coronavirus disease (COVID-19), which may influence their prognosis. Objectives. To assess the role of cardiac injury biomarkers measured on admission and during hospitalization as risk factors for subsequent death in COVID-19 patients. Methods. A systematic review and meta-analysis was carried out involving cohort studies that compared the levels of cardiac injury biomarkers in surviving and dead COVID-19 patients. Cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 57 publications
1
30
0
7
Order By: Relevance
“…Following full-text revision of the remaining 57 articles, 13 were further excluded because they did not meet the inclusion criteria. Thus, 44 studies in 18,856 COVID-19 patients, 14,569 (53% males, mean age 48 years) with low severity or survivor status and 4,287 (59% males, mean age 61 years) with high severity or non-survivor status, were included in the final analysis ( Figure 1 and Table 1 ) ( 7 , 21 63 ). Thirty-two studies were conducted in Asia ( 7 , 22 , 24 , 26 , 27 , 29 , 31 33 , 35 , 38 46 , 48 , 50 , 51 , 53 55 , 57 63 ), eight in Europe ( 25 , 28 , 30 , 34 , 47 , 49 , 52 , 56 ), three in America ( 23 , 36 , 37 ), and one in Africa ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following full-text revision of the remaining 57 articles, 13 were further excluded because they did not meet the inclusion criteria. Thus, 44 studies in 18,856 COVID-19 patients, 14,569 (53% males, mean age 48 years) with low severity or survivor status and 4,287 (59% males, mean age 61 years) with high severity or non-survivor status, were included in the final analysis ( Figure 1 and Table 1 ) ( 7 , 21 63 ). Thirty-two studies were conducted in Asia ( 7 , 22 , 24 , 26 , 27 , 29 , 31 33 , 35 , 38 46 , 48 , 50 , 51 , 53 55 , 57 63 ), eight in Europe ( 25 , 28 , 30 , 34 , 47 , 49 , 52 , 56 ), three in America ( 23 , 36 , 37 ), and one in Africa ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-two studies were conducted in Asia ( 7 , 22 , 24 , 26 , 27 , 29 , 31 33 , 35 , 38 46 , 48 , 50 , 51 , 53 55 , 57 63 ), eight in Europe ( 25 , 28 , 30 , 34 , 47 , 49 , 52 , 56 ), three in America ( 23 , 36 , 37 ), and one in Africa ( 21 ). Thirty-two studies were retrospective ( 7 , 21 23 , 27 , 29 , 31 39 , 41 45 , 48 , 50 , 51 , 53 , 55 , 57 63 ), eight prospective ( 24 , 30 , 46 , 47 , 49 , 52 , 54 , 56 ), whereas the remaining four did not report the study design ( 25 , 26 , 28 , 40 ). Clinical endpoints included disease severity based on current clinical guidelines in 15 studies ( 21 , 24 , 33 , 39 41 , 43 , 48 , 54 , 55 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different works of the literature showed that there is a strong correlation between acute myocardial Injury and COVID-19 infection. New studies are being published from around the globe but the link between acute myocardial injury and COVID-19, the prevalence, reliability of diagnostic modalities, independent predictors, and clinical outcomes are still uncertain and a topic of debate [ 22 , 24 , 26 , [32] , [33] , [34] , [35] , 41 , 44 , 50 , 53 , [57] , [58] , [59] , 62 , 76 , [81] , [82] , [83] , [84] , [85] ].…”
Section: Discussionmentioning
confidence: 99%